2021
DOI: 10.1155/2021/5582615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Phenotypic Tests versus PCR in the Detection of Carbapenemase-Producing Pseudomonas aeruginosa Isolates in Hamadan, Iran

Abstract: In recent years, the prevalence of carbapenem-resistant Pseudomonas aeruginosa isolates has become a worldwide concern. Rapid and accurate detection of carbapenemase-producing P. aeruginosa isolates is so important. The aim of this study was to evaluate the performance of the phenotypic methods such as Modified Hodge test (MHT), CarbaNP (CNPt), combined double-disk synergy test (CDDT), and carbapenem inactivation method (CIM) for rapid and accurate detection of clinical carbapenemase production of P. aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They demonstrated that CIM methods can be used for fast and accurate identification of carbapenemase enzymes. Additionally, this method is suitable to use in medical microbiology laboratories (19). In 2017, Malkoçoğlu et al indicated carbapenemase production was shown in only three of 84 isolates, and noted that the carbapenem resistance in other strains could be due to another mechanism, for example, porin alterations, and efflux pumps (20).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that CIM methods can be used for fast and accurate identification of carbapenemase enzymes. Additionally, this method is suitable to use in medical microbiology laboratories (19). In 2017, Malkoçoğlu et al indicated carbapenemase production was shown in only three of 84 isolates, and noted that the carbapenem resistance in other strains could be due to another mechanism, for example, porin alterations, and efflux pumps (20).…”
Section: Discussionmentioning
confidence: 99%
“…The mCIM test, which is supposed to prove the presence of any carbapenemase type (without differentiating them), lead to negative results for all our tested strains. As the test was performed according to the recommendations [ 27 , 57 , 58 ], we can only assume that the negative results are due to the low-level production of carbapenemase enzymes, even if the genetic background is present in most of the isolates (carbapenemase genes). Thus, the activity of mex efflux pump may play a more important role in bacterial antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mCIM test is described to be a rapid and reliable way to detect carbapenemase-producing bacteria and can be used in clinical laboratories. However, it should be used in conjunction with other laboratory tests and clinical information to make a definitive diagnosis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study documented that the mCIM test is the most sensitive test for the detection of CRE. 30 Beig et al 31 documented Carba NP and mCIM tests as highly sensitive and specific phenotypic tests for detection of CRE with 97% and 94% sensitivity compared to MHT with 67% sensitivity. 31 However, in the present study, both mCIM and Carba NP were highly sensitive in the detection of CRE.…”
Section: Discussionmentioning
confidence: 99%